The virgin of Small Plains : a novel - Pickard, Nancy (New York : Ballantine Books, 2006)
Seventeen years after the discovery of a female murder victim near Small Plains, Kansas, the girl's grave has become the source of strange miracles and legends, until the return of prodigal son Mitch Newquist threatens to bring old secrets to light.
Keywords: Cold cases (Criminal investigation) -- Fiction; Mystery fiction